2017
DOI: 10.1111/cdep.12234
|View full text |Cite
|
Sign up to set email alerts
|

Dealing With Social Difficulty During Adolescence: The Role of Implicit Theories of Personality

Abstract: Social difficulty during adolescence contributes to internalizing problems (e.g., depression, stress) and spurs cycles of aggression and retaliation. In this article, I review how implicit theories of personality—beliefs about whether people can change their socially relevant characteristics—can help explain why some adolescents respond to social difficulty in these ways while others do not. Believing an entity theory of personality—the belief that people cannot change—causes people to blame their own and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
(63 reference statements)
2
29
0
2
Order By: Relevance
“…Vansteenkiste, Simons, Lens, Sheldon, & Deci, 2004)). Respectful language increased adherence—participants consumed 60% more medicine—and sensitivity to respectful language was stronger among those high in endogeneous testosterone (measured via saliva) and also among low-testosterone individuals who were administered testosterone (via nasal spray; Yeager, Hirschi, et al, 2017). This is direct evidence for a key claim of our model: testosterone—a hormone implicated in pubertal maturation—causes an increased behavioral responsiveness to respectful treatment.…”
Section: A Proposed Framework For Understanding and Improving Adolescmentioning
confidence: 55%
See 2 more Smart Citations
“…Vansteenkiste, Simons, Lens, Sheldon, & Deci, 2004)). Respectful language increased adherence—participants consumed 60% more medicine—and sensitivity to respectful language was stronger among those high in endogeneous testosterone (measured via saliva) and also among low-testosterone individuals who were administered testosterone (via nasal spray; Yeager, Hirschi, et al, 2017). This is direct evidence for a key claim of our model: testosterone—a hormone implicated in pubertal maturation—causes an increased behavioral responsiveness to respectful treatment.…”
Section: A Proposed Framework For Understanding and Improving Adolescmentioning
confidence: 55%
“…The model presented here has not yet established the feedback loops through which an intervention that honors the adolescent desire for status and respect might translate into sustained, internalized changes in behavior (though see Fig. 1 in both Yeager, 2017 and Yeager, Purdie-Vaughns, et al, 2017). The question of how time-limited interventions can sustain impact is an emerging topic of investigation in the social and behavioral sciences more generally (Bailey, Duncan, Odgers, & Yu, 2017; Fiske, Frey, & Rogers, 2014; Miller, Dannals, & Zlatev, 2017)…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…“The Growth Factory” is an online intervention that aims to empower adolescents with intellectual disabilities. The intervention is based on scientific research on implicit self-theories and mindset interventions by Carol Dweck and David Yeager [ 16 , 36 , 39 , 51 , 52 ]. A multidisciplinary team of professionals and youth has developed the intervention using a Dutch guideline for effective interventions for people with intellectual disabilities [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Abundant research has shown that lay people differ in their implicit theories about themselves and others, which shapes the way they interpret and react to social situations (Beer, ; Chiu, Hong, & Dweck, ; Droege & Stipek, ; Erdley, Cain, Loomis, Dumas‐Hines, & Dweck, ; Erdley & Dweck, ; Giles & Heyman, , ; Hong, Chiu, Dweck, & Sacks, ; Yeager, ). Some are characterized by an implicit entity theory that construes traits or behaviors as fixed and immutable qualities, and incline to make global, rigid, and enduring judgments of others on the basis of limited information.…”
mentioning
confidence: 99%